Strengthening the Legal Guarantees of Mediation Confidentiality with Contractual Mechanisms - Chitashvili, Natia (Journal of Law, 2023)
Confidentiality is a central essential feature[1] of mediation, a fundamental principle, and one of the most important ethical obligations[2] of a mediator which enhances open, honest communication[3] between the parties and the self-expression of their interests, needs, and concerns in a safe environment.[4] Confidentiality is often an incentive to initiate a mediation process because the interest of confidentiality can be realized from a continuum of dispute resolution systems through the use of the mediation process which ensures the non-disclosure of information. A special interest of a party in confidentiality may be driven by the desire to avoid the precedent of a court decision. The article analyzes the importance of confidentiality in terms of privacy, the obligation of a mediator to inform the parties, and the standards for the safe sharing of confidential information. The article aims to explore the prominence of privacy and legal guarantees, identify possible challenges of implementing confidentiality, and indicate the need to strengthen protection through contractual mechanisms. [1] Deason E.E., The Quest for Uniformity in Mediation Confidentiality: Foolish Consistency or Crucial Predictability, Vol. 85, Issue 1, 2001, 38; Kirtley A., Mediation Privilege Mediation Privilege's Transition from Theory to Implementation: Designing a Mediation Privilege Standard to Protect Mediation Participants, the Process and the Public Interest, Journal of Dispute Resolution, Vol. 1995, Issue 1, 11; Macturk Ch. H., Confidentiality in Mediation: The Best Protection Has Exceptions, 19 Am. J. Trial Advoc., 1995-1996, 424; Harman J., Mediation Confidentiality: Origins, Application and Exceptions and Practice Implications, Australasian Dispute Resolution Journal, 28(2), 2017, 106; Alexsander N., Chong S., Giorgadze V., The Singapore Convention on Mediation, A Commentary, Wolters Kluwer BV, The Netherlands, 2022, 5.97; Schau J.F., View from the Middle of the Road, A mediator’s Perspective on Life, Conflict and Human Interaction, AuthorHouse, 2013, xix. [2] Chen A. (ed.), Zhao Y., Mediation and Alternative Dispute Resolution in Modern China, Springer, Hong Kong, 2022, 63; Turner C.‎, Wählisch M., Rethinking Peace Mediation Challenges of Contemporary Peace-Making Practice, Bristol University Press, 2021, 310; Garner B. (ed.), Black’s Law Dictionary, 8th ed., Thomson West, 2004, 1315; Wendel B. W., Professional Responsibility, Examples and Explanations, Aspen Publishers, United States of America, 2007, 138. [3] Foster T.N., Prentice S., The Promise of Confidentiality in Mediation: Practitioners' Perceptions, Journal of Dispute Resolution, Vol. 2009, Issue 1, 164. [4] Boulle L., Mediation, Principles, Process, Practice, LexisNexis Butterworths, 3rd edition, 2011, 673; Leimguber D., Public Interest and Mediator’s Ethical Dilemma, Australian Dispute Resolution Journal, 24 (3) 2013, 187; Butler V.F., Mediation: Essentials and Expectations, Dorrance Publishing Co., Inc., 2004, 6.